ON THREE-PARAMETER FAMILIES of FILIPPOV SYSTEMS - THE FOLD-SADDLE SINGULARITY - Buzzi, Claudio Aguinaldo [UNESP]; De Carvalho, Tiago [UNESP]; Teixeira, Marco Antonio (World Scientific Publ Co Pte Ltd, 2012)
This paper presents results concerning bifurcations of 2D piecewise-smooth vector fields. In particular, the generic unfoldings of codimension-three fold-saddle singularities of Filippov systems, where a boundary-saddle and a fold coincide, are considered and the bifurcation diagrams exhibited.
Keywords: Fold-saddle singularity; Non-smooth vector field; bifurcation; Unfolding